In order to find b1 from your formula stated we need to do few calculations
A=hb1+hb2, as you wee I multiply h with both bases( b1 and b2)
I will subtract hb2 from both sides
hb1=A-hb2
now I will divide my new expression by h
b1=(A-hb2)/h
4 (e)
sin^8 x - cos^8 x
= (sin^4 x + cos^4 x)(sin^4 x - cos^4 x)
= (sin^4 x + cos^4 x)(sin^2 x - cos^2x)(sin^2 x +cos^2 x)
= (sin^4x + cos^4 x)( sin^2 x- cos^2 x)
Sorry I cant do 4 (d).
Answer:
probably an update which sucks tell me about it lol
(-1,8) is the correct answer I’m pretty sure